PENINGKATAN KUALITAS PEMBELAJARAN IPS MELALUI MODEL THINK PAIR AND SHARE BERBANTUAN VIDEO (Universitas Negeri Semarang, 2014)
Abstrak___________________________________________________________________Tujuan penelitian untuk meningkatkan keterampilan guru, aktivitas siswa, dan hasilbelajar siswa dalam pembelajaran IPS kelas V SDN Gunungpati 02 Semarang.Menggunakan Penelitian Tindakan Kelas Meliputi Perencanaan,Pelaksanaan,Observasidan Refleksi. Teknik pengumpulan data menggunakan tes dan nontes. Analisis datamenggunakan analisis deskriptif kuantitatif dan analisis deskriptif kualitatif Hasilpenelitian menunjukkan: (1) Keterampilan guru siklus I skor 18 kategori cukup, siklus IIskor 25 kategori baik ,siklus III skor 33 kategori sangat baik. (2) Aktivitas siswa siklus Iskor 21,78 kategori cukup, siklus II skor 28,95 kategori baik ,siklus III skor 30.11 kategorisangat baik. (3) Ketuntasan klasikal siklus I 64,11% ,siklus II 71,79%, siklus III 92,3%.(4) afektif siklus I skor 9,63 kategori cukup, siklus 2 skor 11,80 kategori baik,siklus 3 skor13,38 kategori sangat baik.(5) psikomotor siklus I skor 6.49 kategori baik,siklus II skor7,05 kategori baik ,siklus III skor 7,67 kategori baik. Simpulan penelitian adalah melaluimodel Think Pair and Share berbantuan video dapat meningkatkan kualitas pembelajaranIPS meliputi keterampilan guru, aktivitas siswa dan hasil belajar siswa.The research aimed to increase social learning quality of fifth grade students through think pair and share using video. Theresearch was designed using classroom action research in three cycles. Each cycle consisted of planning, acting, observation, andreflection. The techniques used test and nontest. Data analysis using quantitative and qualitative descriptive analysis. The resultshowed: (1) Teacher skills in the first cycle scored 18 with enough category, cycle II scored 25 with good category. Cycle III scored33 with very well category. (2) Students activities scored 21.78 in the first cycle with enough category, it scored 28.95 in secondcycle with good category, it scored 30.11 in the third cycle with very well category. (3) In the first cycle classical completeness was64.11%, 71.79% in second cycle. The third cycle was 92.3%. (4) The affective score was 9.63 in the first cycle with enoughcategory. The second cycle scored 11.80 in good category. It scored 13.38 in the third cycles with very well category. (5) Thepsychomotor score was 6.49 in the first cycle with good category. It scored 7.05 in second cycle with very well category. In thethird cycle scored 7.67 with good category. Conclusions of the research was think pair and share using video improved the qualityof teaching social learning including teacher skills, student activities, and students learning outcomes.